Análisis de la percepción de los residentes de la Parroquia La Unión para la creación de un producto agroturístico en la Hacienda El Porvenir - Parrales Correa, Julexy Jahaira (2021)
The objective of this case is to analyze the perception of the residents of the La Unión parish for the creation of an agro-tourism product on the El Porvenir farm. Community participation is essential when implementing a tourism project because their attitudes will help to know if said plan is viable. For the development of this work, field research was used in order to know the current state of the natural resources that the farm has, it was possible to appreciate that tourists attend this place although its facilities are not completely adequate to carry out some type of tourism. Through this process, it was determined that the El Porvenir farm has natural resources, which could be used to create an agro-tourism product. It is also considered to be an opportunity to promote rural tourism.